The Relationship between Multiple Births and the fall of the Reproductive System and Bladder - حسن سحر; محمد باسل; الرجب عليا (Latakia University Journal -Medical Sciences Series, 2020)
Objective: Evaluate the association between multiple births and various manifestations of urinary and reproductive disorders caused by prolapse. Methods: The study includes 100 married women patients who were reviewing the department of obstetrics and gynecology with a complaint of heaviness in the lower abdomen; lump in the vulva or urinary incontinence. Results: The highest rate of uterine prolapsein multiple births due to multiple births had accumulative effect on the neuromuscular function of the pelvic floor which leads to increased damage over time. Genital prolapse was seen in 71% of normal births compared with 19% of caesarean section patients. The role of episiotomy was shown to prevent anatomical damage to the pelvic floor, as prolapse with episiotomy 21% compared with prolapse without episiotomy 50%. The genital prolapse in women above 50 years old was about 51%. The proportion of genital prolapse in the event of the incidence of lending incense in the abdomen, as a laster and the lobby.